A Cognitive-Behavioral Model of Apathy in Parkinson’s Disease - Olivia Plant; Annika Kienast; Daniel S. Drew; Elitsa D. Slavkova; Kinan Muhammed; Helen Kennerley; Masud Husain (Parkinson's Disease)
Apathy is recognized to be a common, disabling syndrome that occurs across a range of psychiatric and neurological conditions, including Parkinson’s disease. It can have a significant impact on quality of life, both for people affected and those around them. Currently, there are no established, evidence-based treatments for this debilitating syndrome. Assessment and treatment have been complicated by overlaps with depression and anhedonia, as well as a lack of understanding of the underlying mechanisms. Emerging lines of evidence conceptualize apathy as a reduction of motivation associated with disordered effort-based decision-making and dysfunction of distinct neural circuitry between the basal ganglia and medial prefrontal cortex. Here, we introduce a novel cognitive-behavioral framework that can inform a clinician’s conceptualization and treatment of apathy, using cognitive-behavioral therapy (CBT) techniques. We focus on people with Parkinson’s disease in our model, but our approach is transdiagnostic and can be applied to other conditions. It considers both individual targets for therapy as well as maintenance and intervention at a systemic level. The generalizability and parsimony of the framework provides a structured assessment and formulation of apathy, while also allowing clinicians to remain sensitive to other neuropsychiatric symptoms that can occur alongside apathy, such as depression and anxiety.